2022
DOI: 10.1186/s43141-022-00413-5
|View full text |Cite
|
Sign up to set email alerts
|

An in silico pipeline approach uncovers a potentially intricate network involving spike SARS-CoV-2 RNA, RNA vaccines, host RNA-binding proteins (RBPs), and host miRNAs at the cellular level

Abstract: Background In the last 2 years, we have been fighting against SARS-CoV-2 viral infection, which continues to claim victims all over the world. The entire scientific community has been mobilized in an attempt to stop and eradicate the infection. A well-known feature of RNA viruses is their high mutational rate, particularly in specific gene regions. The SARS-CoV-2 S protein is also affected by these changes, allowing viruses to adapt and spread more easily. The vaccines developed using mRNA codi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…The suggested analytical pipeline revealed that the mere presence of the "Togaviridae, Flaviviridae, and Bunyaviridae" genomes in the host cell could predict the depletion of particular RBPs and that the depletion of these protein could change metabolic pathways related to the clinical phenotype. Different positive and negative single-strand RNA viruses can sequester RBPs from host proteins to speed up the replication process, disrupts nucleus-cytoplasmic traffic and leads to a spatial redistribution of proteins from the nucleus to the cytoplasm, altering the host cell network [62,63]. It has been demonstrated via individual RBP analysis that dysregulation is related to clinical manifestations such as neuropathy, weakness, and, in severe cases, encephalitis by infecting host neurons.…”
Section: Discussionmentioning
confidence: 99%
“…The suggested analytical pipeline revealed that the mere presence of the "Togaviridae, Flaviviridae, and Bunyaviridae" genomes in the host cell could predict the depletion of particular RBPs and that the depletion of these protein could change metabolic pathways related to the clinical phenotype. Different positive and negative single-strand RNA viruses can sequester RBPs from host proteins to speed up the replication process, disrupts nucleus-cytoplasmic traffic and leads to a spatial redistribution of proteins from the nucleus to the cytoplasm, altering the host cell network [62,63]. It has been demonstrated via individual RBP analysis that dysregulation is related to clinical manifestations such as neuropathy, weakness, and, in severe cases, encephalitis by infecting host neurons.…”
Section: Discussionmentioning
confidence: 99%
“…The suggested analytical pipeline revealed that the mere presence of the “ Togaviridae , Flaviviridae , and Bunyavirales ” genomes in the host cell could predict the depletion of particular RBPs and that the depletion of these proteins could change metabolic pathways related to the clinical phenotype. Different positive and negative single-strand RNA viruses can sequester RBPs from host proteins to speed up the replication process, disrupt nucleus-cytoplasmic traffic, and lead to a spatial redistribution of proteins from the nucleus to the cytoplasm, altering the host cell network [ 57 , 58 ]. It has been demonstrated via individual RBP analysis that dysregulation is related to clinical manifestations such as neuropathy, weakness, and, in severe cases, encephalitis by infecting host neurons.…”
Section: Discussionmentioning
confidence: 99%